Design of a new type of overshoot elimination system of transient electromagnetic transmitter - HAN Bing; YU Shengbao; SUN Ha (Gong-kuang zidonghua, 2014)
In view of problem of detection blind area caused by overshoot of transmitting current of transient electromagnetic transmitter, the paper proposed a design scheme of a new type of overshoot elimination system of transient electromagnetic transmitter. An optimal RLC second-order circuit is paralleled at two ends of transmitting coil, the circuit is connected when the transmitting current decreases close to zero, which makes the transmitting current accord to exponential decay, so as to eliminate current overshoot effectively. The simulation and experiment results show that the scheme can eliminate overshoot oscillation of the transmitting current and reduce detection blind area.